Diseño de una guía didáctica del uso de las tic's como estrategia metodológica para fortalecer los procesos enseñanza - aprendizaje dirigida a los docentes de la escuela “Simón Bolívar”, de la parroquia la matriz, del cantón Latacunga, provincia de Cotopaxi en el período 2012 – 2013 - Cadena Lara, Ana del Pilar (2015)
The relationship between TIC’s and education has two aspects; the first one citizen are forced to know and learn about TIC’s; therefore they can be applied to the educational process. The teachers should be aware that the computer is a tool to solve problems in the teaching – learning by practices in different subjects, is a new medium for teaching and will also be applied as an appropriate teaching strategy to improve educational quality. The teacher’s role is to put technology at the service of the student to create a context of activity in order to from a holistic beings, these technologies are increased knowledge and demands a high level of education constantly updated become a permanent requirement. Throughout the development of this work addressed issues of great importance to know the information about technology and communication and its use as a methodological strategy to strengthen the teaching – learning process aimed at teachers from “Simon Bolivar” School.